Analysis of Place Attachment and Planned Behavior In Kopi Tuku - Kelvin Alexander; Anna Amalyah Agus (Green Publisher Indonesia, 2025)
This study aims to analyze the relationship between Place Attachment Theory and Planned Behavior Theory in predicting consumer repurchase intention for Tuku Coffee products. In particular, this study explores the influence of the dimension of place attachment, namely cognitive place identity, affective place identity, and place dependence, as well as the components of TPB which include attitudes, subjective norms, perception of behavioral control, and behavioral intentions. A quantitative approach is used in this study with an explanatory research design. Sampling was carried out using purposive sampling techniques, with sample size determined based on the 10-times rule in Partial Least Squares Structural Equation Modeling (PLS-SEM). Data analysis was carried out using PLS-SEM to test the causal relationship between the variables studied. The results showed that seven of the nine hypotheses put forward were supported, while two hypotheses were rejected. These findings contribute to the consumer behavior literature by confirming the important role of PAT and TPB in shaping repurchase intent. The practical implications of this study provide strategic direction for coffee industry players, especially Kopi Tuku in building emotional attachment with consumers, increasing customer loyalty, and designing marketing strategies that are oriented towards consumer experience and sustainability. Overall, this research offers valuable theoretical and managerial insights in the context of the rapidly growing coffee industry.